Effect and validation of plate thickness dimensional effects on grouting compactness in bridge ducts based on ultrasonic testing - Chao Feng; Miren Rong; Yinping Pang; Hailong Wang; Lanxin Luo; Zhikun Xue; Ying Yuan; Dongyang Geng; Jiayin Li (PLoS ONE, 2025)
Based on the theory of ultrasonic non-destructive testing, this study investigates the dimensional effect of plate thickness on the detection of grouting compactness in prestressed bridge ducts. By combining finite element simulation with engineering case validation, a high-precision time-domain analysis model is proposed to qualitatively and quantitatively evaluate the grouting compactness of prestressed bridge pipeline with varying plate thicknesses. This study employs ABAQUS finite element software to simulate and analyze the excitation, propagation, and reception characteristics of ultrasonic waves in concrete structural components. A time-domain analytical theoretical model is established to evaluate the detection results of pipelines with various defects. By comparing the simulation results of the theoretical model with actual engineering detection cases, the time-domain analytical theoretical model demonstrates high feasibility and reliability. The results indicate that the time-domain analysis method achieves high accuracy when utilizing the correlation between plate thickness and the first wave acoustic time. This approach enables both qualitative and quantitative analysis of pipeline density using ultrasonic non-destructive testing, thereby improving the accuracy and efficiency of damage assessment for prestressed pipe grouting compactness.